The effectiveness of strength-based counseling on the reduction of divorced women's depression - Darbani, Seyed Ali; Parsakia , Kamdin (Journal of Assessment and Research in Applied Counseling (JARAC), 2022)
Background and Aim: Divorce is one of the most stressful losses and causes emotional derangement and behavioral problems in individuals. Although the negative consequences of divorce tend to bind both couples, but based on studies, the vulnerability of women after divorce is greater than men; therefore, this study aimed to examine the effectiveness of strength-based counseling on the reduction of divorced women's depression.  Methods: This study is a quasi-experiment an was performed based on pretest and post-test with a control group (10 in the experimental group and 10 in 10 in the control group). The statistical population of this study was divorced women who attended to Mehravar counseling center of Tehran in the second half of 1400 because of their depression. The data collection tool in the present study was the Beck depression inventory 2 (1996). ANOVA with repeated measure was used to analyze the data. Results: Based on the results obtained in the pre-test stage, there was no significant difference between the experimental and control groups in terms of depression. But after the intervention (Smith’s (2006) strength-based intervention) a significant difference (P = 0/006, F = 13.78) was observed between the two groups and this effect was sustained in follow-up stage. Conclusion: According to results, it can be concluded that strength-based counseling reduces the level depression in divorced women. Thus, using this approach is suggested in order to reducing depression of divorced women